THE EFFECT OF ABATACEPT ON BLOOD BIOMARKERS IN PATIENTS WITH RHEUMATOID ARTHRITIS - M. A. Borisova; G. V. Lukina; Ya. A. Sigidin; E. L. Luchikhina; D. E. Karateev; A. A. Novikov; E. N. Aleksandrova; M. V. Cherkasova; E. S. Aronova; S. L. Glukhova; E. L. Nasonov (Научно-практическая ревматология, 2017)
Objective: to estimate changes in the cytokine profile in patients receiving abatacept (ABC).Subjects and methods. The investigation enrolled 44 patients with rheumatoid arthritis (RA) who had been unsuccessfully treated with disease-modifying antirheumatic drugs and biological agents. A control group included 16 healthy donors. The majority of patients were women who were positive for rheumatoid factor (RF) (80%) and antibodies to cyclic citrullinated peptide (ACCP) (79.5%); the mean age was 49.6±13.9 years; the median disease duration was 2 [1.4; 3] years with high RA activity (mean DAS28, 5.2±0.8). The serum concentrations of interleukin (IL) 1β, IL-6, IL-17AF, tumor necrosis factor-α (TNF-α), VEGF-A, IP-10, and YKL-40 were measured by enzyme immunoassay before and 6 months after ABC therapy. Disease activity was assessed using DAS28 every 3 months. ABC was infused intravenously according to the standard regimen.Results and discussion. The patients with RA as compared with the control group had significantly elevated levels of IL-6 (2.4 [1.1; 6.4] and 0.7 [0.62; 1.0] pg/ml; p=0.0002), YKL-40 (97 [68.4; 97.9] and 64 [52.4; 107.5] pg/ml; p=0.03), IP-10 (21 [12.9; 49.8] and 14 [9.2; 15.2] pg/ml, respectively; p=0.005). ABC caused a significant decrease in RA activity after 3 months of therapy (p<0.05). Following 6 months, 86% of the patients achieved good and moderate EULAR responses; low RA activity according to DAS28 was recorded in 52%. ABC induced significant decreases in the concentrations of IL-6 to 1.29 [0.9; 2.2] pg/ml (p=0.0006) and IP-10 to 14 [7.5; 28] pg/ml (p=0.007) after 6 months of therapy. A similar trend was observed when assessing changes in the concentration of matrix metalloproteinase 3 (MMP-3), which reduced from 30.1 [13; 82] to 10 [7.4; 55] pg/ml (p=0.0003), and in that of RF, which declined from 218 [9.6; 187] to 159 [9.7; 155] pg/ml (p=0.02). The lower levels of IL-6 (r=0.5) and IP-10 (r=0.32) significantly correlated with a decrease in DAS28 (p<0.05). There was a trend towards a more pronounced reduction in disease activity in patients positive for ACCP and antibodies to modified citrullinated vimentine (AMCV). The percentage of non-responders to therapy in the ACCP- and AMCV-negative groups was nearly twice as high as in those who were positive for these antibodies (27.2 and 16%; 26.7 and 14.8%, respectively), but these differences failed to reach significance. However, after 6-month of follow-up, the percentage of non-respondents in the AMCV-negative group was significantly higher than in the AMCV-positive group (20% and 0%, respectively; p=0.03). The patients who did not respond to ABC therapy had higher baseline levels of IL-6 (p=0.03) and YKL-40 (p=0.02). Conclusion. ABC therapy results in a substantial reduction in the concentration of the proinflammatory cytokines IL-6 and IP-10, as well as MMP-3 and RF. The lower levels of IL-6 and IP-10 significantly correlated with a decrease in RA activity. There was a tendency towards a more pronounced reduction of disease activity in ACCP- and AMCV-positive patients. The high baseline levels of IL-6 and YKL-40 and the absence of AMCV may suggest that ABC therapy can be ineffective.